Pemanfaatan Lego pada Pembelajaran Pola Bilangan - Sri Handayani; Ratu Ilma Indra Putri; Somakim Somakim (Universitas Syiah Kuala, 2015)
This study aimed to generate learning trajectories in learning number patterns by using lego in grade IX SMP. This study was conducted in SMP N 1 Tanjung Raja. The method of this study was design research consisted of three phases, i.e. preliminary, design experiment (pilot experiment and teaching experiment) and retrospective analysis. In this study, a series of instruction was designed and developed based on conjecture of learning processes and PMRI approach. In this paper discussed was teaching experiment phase. Results of this research was learning trajectory that includes a series of learning process that were activity constructs patterns by using Lego generate sequence to determine rules and the next number of sequence, activity outlines pattern to determine the n-th pattern of sequence, until activity number patterns to determine the amount of n tribe/number. Based on the activities undertaken in this study could help students to understand number patterns.